2018
DOI: 10.1038/s41418-018-0084-9
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA CASC9 promotes esophageal squamous cell carcinoma metastasis through upregulating LAMC2 expression by interacting with the CREB-binding protein

Abstract: Esophageal squamous cell carcinoma (ESCC) is the main subtype of esophageal cancer. Long noncoding RNAs (lncRNAs) are thought to play a critical role in cancer development. Recently, lncRNA CASC9 was shown to be dysregulated in many cancer types, but the mechanisms whereby this occurs remain largely unknown. In this study, we found that CASC9 was significantly upregulated in ESCC tissues, with further analysis revealing that elevated CASC9 expression was associated with ESCC prognosis and metastasis. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
157
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(167 citation statements)
references
References 49 publications
7
157
0
Order By: Relevance
“…The next step was to investigate the molecular mechanism by which GPC3‐AS1 and GPC3 were all highly expressed in CC cell lines. Recently, the transcription factor mechanism has attracted the increasing attention as a result of its contribution to the up‐regulation of lncRNA . Hence, we chose four transcription activators (ELK1, STAT3, SP1 and EGR1) to explore whether these factors participate in the up‐regulation mechanism of GPC3‐AS1 and GPC3 in CC cells.…”
Section: Resultsmentioning
confidence: 99%
“…The next step was to investigate the molecular mechanism by which GPC3‐AS1 and GPC3 were all highly expressed in CC cell lines. Recently, the transcription factor mechanism has attracted the increasing attention as a result of its contribution to the up‐regulation of lncRNA . Hence, we chose four transcription activators (ELK1, STAT3, SP1 and EGR1) to explore whether these factors participate in the up‐regulation mechanism of GPC3‐AS1 and GPC3 in CC cells.…”
Section: Resultsmentioning
confidence: 99%
“…19 Further explorations demonstrated that CASC9 can promote ESCC growth, migration, invasion, and metastasis by regulating molecular pathways, such as LAMC2 and EZH2. 20,21 CASC9 also plays an oncogene in many other malignancies such as gastric cancer and nasopharyngeal cancer. 22,23 Our results confirmed the high expression level of CASC9 in ESCC tumor tissues, and trans-analysis inferred the potential regulatory correlation of CASC9 with MYZAP, a myocardial-related gene.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies showed that this lncRNA is overexpressed in multiple types of cancers [38][39][40] . Overexpression of this lncRNA promotes cancer cell growth 50 , invasion 51 and metastasis 52 . Here, we discovered that methylation loss of its promoter is a principle molecular mechanism of ESCCAL-1 dysregulation in ESCC.…”
Section: Discussionmentioning
confidence: 99%